TRANSCENDENCE AND IMMANENCE: A COMPARATIVE ANALYSIS OF DIVINE ATTRIBUTES IN MONOTHEISTIC RELIGIONS - Liu, Sophie (European journal for philosophy of religion, 2024)
Since mankind hide the truth because they are unjust, God's wrath is shown from heaven against all of their immorality. Because God has revealed to them everything, they can know about him, it is obvious to them. Since the beginning of time, his intangible qualities, namely, his everlasting power and divine nature, have been evident in the things that have been created. Thus, they have no justification. Because even though they were aware of God, they did not revere or express gratitude to him; instead, their hearts became darkened and their thinking became pointless. Therefore, it is obviously incorrect to consider God's transcendence to be a sort of fog that obscures God from human perception. Indeed, verses in the Bible highlight God's mystery and incomprehensibility, such "Oh, the depth of the riches and wisdom and knowledge of God!" How inexplicable his methods and how unsearchable his judgements! Because no one has ever understood the Lord's thoughts or served as his counsellor. Or has someone given him a present for which he may receive payment? Because everything comes from him, through him, and to him. Glory eternally to him. Amen. His "immanence," not his "transcendence," is enigmatic in this line. Even if God's historical facts are unfathomable, Paul is nonetheless able to explain them in understandable terms. He informs the Roman church of what they are unaware of and the reason for it. "Known unknowns" are the unknowns. Furthermore, a mystery involving a God otherwise "clearly" understood is always a mystery. If God's transcendence does not impede our understanding of him or our ability to articulate him clearly, how should we describe it? "On high" or "in Heaven," as used in the Bible, consistently alludes to God's regal status.